Pelatihan Peningkatan Kapasitas Untuk Mewujudkan Pelayanan Prima Di Desa Tulungrejo Kabupaten Blitar - Restu Karlina Rahayu; Tia Subekti; Mayuko Galuh Mahardika (Universitas Muhammadiyah Sidenreng Rappang, 2026)
A community service initiative was conducted in Tunggulrejo Village, Blitar Regency, in June 2025. The program involved the village secretary, village officials, neighborhood association (RT), community association (RW), the Village Consultative Body, and the Village Community Empowerment Institution. Twenty-five participants attended this capacity-building training. The training was motivated by the significant tourism potential of Tunggulrejo Village, including attractions such as the Mount Kelud trekking and climbing track, Loji Pine Forest, and Mount Kawi, which are expected to draw numerous visitors. In addition to serving the local community, village officials must also be equipped to address the needs of tourists. As the most immediate level of government, the village administration plays a critical role in delivering essential services, particularly administrative support. Achieving high-quality service requires specific competencies, such as maintaining a professional appearance, demonstrating friendliness, responsiveness, impartiality, punctuality, responsibility, and proficiency in assigned tasks. Furthermore, service providers must be capable of managing complaints to ensure appropriate follow-up for any services perceived as unsatisfactory. Blitar Regency comprises 22 sub-districts, 220 villages, 28 urban villages, and 759 hamlets. In 2023, Tunggulrejo Village had a population of 2,435, with most residents engaged in farming and livestock activities.